Implications of the Association Agreement with the European Union on the Financial Public Management in the Republic of Moldova - Lilia Rotaru; Iulia Caprian; Tatiana Covalschi (CES Working Papers, 2015)
European integration is not just a goal of the foreign policy of the Republic of Moldova, but also a natural aspiration of an European nation to join the European family and the signing of the Association Agreement between Moldova and the European Union is an important step in achieving this goal. The Republic of Moldova has developed and continues to promote rigorous reforms in the area of public finance management. In this article we have analyzed the main reforms and achievements in the field of public finance management in the Republic of Moldova, their importance by reference to good European practices, but also the need to continue them in the context of signing the Association Agreement. The authors argue that until now, the public finance management reform had been focused mainly on the planning and execution phases of National Public Budget, nonetheless the main problems lay in poor budgetary reporting and control. Corruption and fraud are the main risk areas for all the promoted reforms. The conclusion of this paper is that the most urgent actions that should be undertaken consist in improving public procurement procedures, enhancing the internal control, financial inspection and external audit. Only in such a way trustful relation with EU could be created and this is particularly important as it could permit to absorb more European funds to invest in the economic and social development in our country.
Keywords: F36; H61; H83; 330; European integration; Association Agreement; public finance management reform